The Impact of Service Digitalization and Cashless Payments on Operational Efficiency: A Millennial and Gen Z Consumer Perspective - Nurul Aziz Pratiwi; Minhajuddin Minhajuddin; Kenny Nabila Putri (Jurnal Wacana Ekonomi, 2026)
This study aims to analyze the effect of service digitalization and cashless payment on operational efficiency from the perspective of Millennial and Generation Z consumers. A quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The sample consisted of 200 respondents consisting of Millennial and Gen Z consumers in West Java who actively use digital services and cashless payment systems. Outer model testing results confirmed that all research instruments satisfied convergent validity (loading factor > 0.70; AVE > 0.50), discriminant validity, and reliability (Cronbach's Alpha and Composite Reliability> 0.70). Inner model results revealed that service digitalization had a positive and significant effect on operational efficiency with a path coefficient of 0.597 (T-statistic = 7.501; p = 0.000), while cashless payment also showed a positive and significant effect with a path coefficient of 0.313 (T-statistic = 3.682; p = 0.000). An R² value of 0.758 indicates that both variables collectively explain 75.8% of the variation in operational efficiency. Service digitalization proved to be the more dominant predictor with a large effect size (f² = 0.501) compared to cashless payment (f² = 0.137). The novelty of this study lies in its simultaneous examination of both service digitalization and cashless payment as co-determinants of consumer-perceived operational efficiency within a generational comparative framework an approach that remains underexplored in the extant literature. These findings provide empirical evidence that increased adoption of digital service technology and cashless payment systems significantly enhances the perceived operational efficiency of young consumers in the digital era. Future research is encouraged to address the current generational sampling imbalance (Gen Z: 69.5%; Millennials: 30.5%) and expand geographic coverage beyond West Java.